The Simplified Reference Tissue Model with F-Fallypride Positron Emission Tomography: Choice of Reference Region - Kenji Ishibashi; Chelsea L. Robertson; Mark A. Mandelkern; Andrew T. Morgan; Edythe D. London (Molecular Imaging)
The development of high-affinity radiotracers for positron emission tomography (PET) has allowed for quantification of dopamine receptors in extrastriatal and striatal regions of the brain. As these new radiotracers have distinctly different kinetic properties than their predecessors, it is important to examine the suitability of kinetic models to represent their uptake, distribution, and in vivo washout. Using the simplified reference tissue model, we investigated the influence of reference region choice on the striatal binding potential of 18 F-fallypride, a high-affinity dopamine D 2 /D 3 receptor ligand. We compared the use of the visual cortex and a white matter region (superior longitudinal fasciculus) to the cerebellum, a commonly used reference tissue, in a PET-fallypride study of healthy and methamphetamine-dependent subjects. Compared to the cerebellum, use of the visual cortex produced significantly greater sample variance in binding potential relative to nondisplaceable uptake (BP ND ). Use of the white matter region was associated with BP ND values and sample variance similar to those obtained with the cerebellum and a larger effect size for the group differences in striatal BP ND between healthy and methamphetamine-dependent subjects. Our results do not support the use of the visual cortex as a reference region in 18 F-fallypride studies and suggest that white matter may be a reasonable alternative to the cerebellum as it displays similar statistical and kinetic properties.